2020
DOI: 10.1177/0963721420906218
|View full text |Cite
|
Sign up to set email alerts
|

Formal and Informal Supports for Managing Work and Family

Abstract: Many working adults manage joint work and family responsibilities and turn to supports offered at work and in the home to help manage these roles successfully. We review the current evidence on supports for improving work–life outcomes, including informal support from people at work and at home as well as formal organizational and national policies. Informal support is consistently moderately associated with better work–family experiences. Despite popular emphasis on formal policies, evidence for their effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 39 publications
3
54
0
3
Order By: Relevance
“…The recent study depicted that individuals who experience greater workfamily conflict when work and home boundaries are violated as the boundary violations hinder one from meeting the work goal and also resulted in greater negative effect (Hunter et al, 2017). Other studies have shown the utilization of the policy could result in greater expectation from role senders (i.e., family members) on a focal person to perform more family tasks such as carrying out household work and taking care of children and the elderly (Allen et al, 2013;French & Shockley, 2020;Greenhaus & Beutell, 1985;Tausig & Fenwick, 2001). Despite past research reported that familyfriendly policy such as flexitime could help to release work-family conflict (Shockley & Allen, 2010), however, telework policy use that involving high integration of work-family boundaries has not been seen as a remedy for mitigating the work-family conflict in Kossek et al (2006) and Abendroth and Reimann (2018) studies.…”
Section: Family-friendly Policy Work-family Boundary Management and Work-family Conflictmentioning
confidence: 99%
See 4 more Smart Citations
“…The recent study depicted that individuals who experience greater workfamily conflict when work and home boundaries are violated as the boundary violations hinder one from meeting the work goal and also resulted in greater negative effect (Hunter et al, 2017). Other studies have shown the utilization of the policy could result in greater expectation from role senders (i.e., family members) on a focal person to perform more family tasks such as carrying out household work and taking care of children and the elderly (Allen et al, 2013;French & Shockley, 2020;Greenhaus & Beutell, 1985;Tausig & Fenwick, 2001). Despite past research reported that familyfriendly policy such as flexitime could help to release work-family conflict (Shockley & Allen, 2010), however, telework policy use that involving high integration of work-family boundaries has not been seen as a remedy for mitigating the work-family conflict in Kossek et al (2006) and Abendroth and Reimann (2018) studies.…”
Section: Family-friendly Policy Work-family Boundary Management and Work-family Conflictmentioning
confidence: 99%
“…Kailasapathy and Metz's (2012) study revealed that subordinates are more likely than supervisors to initiate negotiation about the work-family life arrangements which involve exchange relationships at work. Self-regulation is needed when access to family-friendly policy to juggle work and family role responsibilities (French & Shockley, 2020). Individuals engage in negotiation to collaborate with their role partners at workplace, supervisor and coworkers for seeking integrative solutions, flexible work arrangements, coordinate work and work schedule leave arrangements and the use of work-family benefits, and negotiation with a spouse or other family members at home to achieve their desired work and family life arrangements (Kirby & Krone, 2002;Robertson et al, 2019;Ter Hoeven et al, 2017).…”
Section: Moderating Effect Of Work-family Boundary Negotiationmentioning
confidence: 99%
See 3 more Smart Citations